SOCIAL MARKETING STRATEGY VOLUNTEER EXPERIENCE IN HANDLING CLEFT LIP AND PALATE PATIENTS (CLPP) IN JEMBER AND BONDOWOSO DISTRICT - Ulfa Elfiah (UPT Penerbitan Universitas Jember, 2017)
Background: The reality shows that people with cleft lip and palate initially refuse to perform surgery. The reason are 1) the patient feels fear because the myth of the operation is dangerous; 2) the myth of skin for operation is taken from the thigh; 3) they feel afraid that they cannot pay operating costs because it is very expensive and 4) there is information if a patients do examination in the hospital only for taking photographs but no realization for treatment. This study aims to describe the meaning of social marketing strategy experience of a volunteer in handling cleft lip and palate in Jember and Bondowoso. Methods: Qualitative research with phenomenology design using in-depth interview technique on two participants with characteristics: 1) social marketing volunteer; 2) understand and be able to speak Indonesian; 3) expressed willingness to become a participant. Results: The research produced four strategic themes that it is used by social workers to assist in handling cleft lip and palate patients. The strategy included knowing the causes of delay in surgery, making a network, generating trust in patients, using media as tool or way of communicating with society. Conclusions: Social marketing volunteer experience in Jember and Bondowoso is very spesific with using four strategies as key to success supporting and handling society with cleft lip, and palate willing to do the operation. This strategies can be adopted as the approach of health worker such as nurses in overcoming health problems. Keywords: phenomenology, cleft lip, and palate, volunteer social marketing, strategy